ANALYSIS OF THE CREATIVE THINKING ABILITY OF PGSD STUDENTS IN OPEN-ENDED PROBLEM-BASED GEOMETRY LEARNING - Suastika, I Ketut; Puspasari, Yovita; Hariyani, Sri; Primasatya, Nurita (JME (Journal of Mathematics Education), 2024)
The ability to think creatively is an important skill in the world of education, especially for students of the Primary School Teacher Education Study Program (PGSD). In learning mathematics, especially geometry, this ability is crucial for understanding concepts in depth and solving problems innovatively. However, there are still many students who show limitations in generating creative ideas, especially in the aspects of originality and elaboration. Therefore, this research aims to analyze the creative thinking abilities of PGSD students in open problem-based geometry learning, which gives students the freedom to explore various solutions in solving geometric problems. This research uses descriptive qualitative methods with data obtained through interviews, observation and document analysis. Research informants include lecturers, PGSD students, heads of study programs, librarians, and the curriculum development team at STKIP PGRI Trenggalek. The research results show that the open problem-based learning method is effective in improving students' fluency and flexibility abilities. However, in the aspects of originality and elaboration, several obstacles were still found that required more intensive guidance and the use of supporting technology. With the right approach, this method can be a solution to optimize students' creative thinking abilities in learning geometry.